2017
DOI: 10.1177/1558944717708029
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Assisted Resection of Triangular Fibrocartilage Complex Lesions: A 19-Year Follow-up

Abstract: This study demonstrates persisting satisfactory subjective and functional outcomes for patients following arthroscopic assisted resection for lesions of the TFCC at 19 years of follow-up. Arthroscopically assisted resection of selected TFCC lesions seems to be both a safe and efficient procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In this analysis, 302 patients underwent TFCC debridement in 10 articles of a variety of Palmer types (178 1A, 53 1B, 14 1C, 28 1D with 43 unclassified Type 1) which were not separated for results and sometimes represent multiple lesions in the same patient. 9,15,[29][30][31][32][33][34][35][36] All were done arthroscopically. Three of these articles used the Mayo wrist classification to evaluate patient outcomes, and among the 75 patients in these studies, 30 patients demonstrated excellent, 29 good, 9 fair, and 7 poor outcomes.…”
Section: Debridementmentioning
confidence: 99%
“…In this analysis, 302 patients underwent TFCC debridement in 10 articles of a variety of Palmer types (178 1A, 53 1B, 14 1C, 28 1D with 43 unclassified Type 1) which were not separated for results and sometimes represent multiple lesions in the same patient. 9,15,[29][30][31][32][33][34][35][36] All were done arthroscopically. Three of these articles used the Mayo wrist classification to evaluate patient outcomes, and among the 75 patients in these studies, 30 patients demonstrated excellent, 29 good, 9 fair, and 7 poor outcomes.…”
Section: Debridementmentioning
confidence: 99%
“…The MMWS was reported in 11 arthroscopic repair studies (n ¼ 299), 2,3,8,15,17,18,20,25,30,33,34 7 open repair studies (n ¼ 154), 2,3,8,10,31,35,36 and 4 debridement articles (n ¼ 118). 26,27,37,38 Preoperative mean scores were 54.2 for arthroscopic repair studies and 48.5 for open repair studies (no preoperative scores were reported in debridement studies); postoperative scores were 84.0, 79.9, and 88.6, respectively.…”
Section: Clinical Outcomesmentioning
confidence: 99%